IMPLEMENTASI PROGRAM PENGHIJAUAN DI PT SEMEN BATURAJA (PERSERO) Tbk. - Rindy Putri Hapsari; Safaruddin Safaruddin (Fakultas Ilmu Sosial Dan Politik, Universitas Wijayakusuma Purwokerto, 2022)
Reforestation is an effective and efficient activity to reduce global warming and reduce carbon emissions. Reforestation efforts are often carried out by several agencies, including the Government, State-Owned Enterprises (BUMN), the private sector, and other institutions. This study aims to investigate the successful implementation of the reforestation program at PT Semen Baturaja (Persero) Tbk. The method used in this research is descriptive qualitative, using the implementation model proposed by Ripley and Franklin. Findings in the field indicate that the implementation of the reforestation program at PT Semen Baturaja (Persero) Tbk has been successful and shows optimal results. This success is tested through a study of three dimensions of successful implementation, namely the level of compliance, smooth functioning, performance, and impact of the reforestation program. The success of the implementation can also be seen from the level of employee compliance with the greening SOPs applied, the implementation of silviculture-based reforestation routines, and the achievement of targets and standards for the number of seeds planted. In addition, Semen Baturaja has also succeeded in distributing seeds to communities around the company such as Non-Governmental Organizations (NGOs), educational institutions, and environmentalists or nature lovers.